ISO/IEC 29110 and Software Engineering Education: A Systematic Mapping Study - Vives, L. (2022)
Abstract: This article presents a study of the publications made on the ISO/IEC 29110 standard in the university context, especially from the perspective of software engineering education. ISO 29110 is a life cycle profiles for very small entities on systems and software engineering standard, published in many parts. ISO 29110, since its publication in 2011 and its continuous evolution to these days, is the subject of study in different contexts, with education being a relevant axis. Considering, that software engineering education has implications in the software industry in emerging countries, it is necessary to identify and consolidate the work done in this context. In this study, the main research question was what researches have been done at ISO 29110 in the training of software engineers? To answer this question, a systematic mapping study (SMS) was performed. In the SMS, 241 articles were obtained with search string and 17 of them became as primary study after a process selection. Based on these studies, it was possible to determine that the software engineering Basic profile of ISO 29110 and its processes (Project Management and Software Implementation) have been the most studied. Besides, it was identified that project-oriented learning and gamification techniques have been the most used ISO 29110 learning strategies in the training of future software industry professionals.